PENGARUH TERMAL TERHADAP DEGRADASI LEMPENG PVC DENGAN KOMPOSISI TERTENTU - Ariful Amri, T.
Research about the thermal influence on PVC films with certain compositions has been carried out. The first composition was made by mixing 85 PVC resin Ryuron K-70, 13 % plasticizer DOP, and 2% stabilizer TMF-125. The second composition was made by mixing 85 % PVC resin Ryuron K-70, 15 % plasticizer DOP, without the addition of stabilizer TMF-125. Some of the PVC films were irradiated by UV light, and some others were heated at temperatures 30°C, 60°C, 80°C .and 100°C, respectively, for the 1st and 2nd composition. Sampling was carried out every 12 days since nil day up to 48th day, then the tensile strength and the intrinsic viscosity were investigated and the UV spectra, the IR spectra and X-ray difractogrammes were made. The results showed that PVC films irradited by UV light, and by heating at temperatures 30°C, 60°C, 80°C, and 100°C, will decrease the tensile strengthr intrinsic viscosity, and the degree of cristallinity, and will in-crease the specific absorptivity at 255 nm (A255/C), 290 nm (A290/C), and optical density D1720/D2900. From these results it can be concluded, that PVC films irradiated by UV light and Mated at the above mentioned temperatures were degraded. The resistance of the 1st composition was higher than 2nd composition, and the influence of heating at 30°C, were found to be lower than that of irradiation by UV light.